KAJI EKSPERIMENTAL PERFORMANSI PENGEREMAN KAMPAS REM KOMPOSIT SERAT BONGGOL JAGUNG DALAM KEADAAN BASAH SEBAGAI BAHAN ALTERNATIF KAMPAS REM MOTOR - Rochim Nofian; Budi Harjanto; Yuyun Estriyanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
The study aims to: (1) Investigate the effect of variations in the composition of composites of corn and brass powder brake pads on the coefficient of friction in wet test. (2)Investigate the variations of composite corn and brass powder brake pads which have the highest coefficient of friction in wet conditions. (3)Investigate the ratio braking performance of brake lining composite corncob powder with comparison brake lining. This research is an experimental research with analysis data use descriptive quantitative method. Data were obtained by using Prony Brake engine braking performance test. This research specimen is variation in the composition of brake lining material, namely: first composition with a composition of 20% corncob powder, 40% brass powder, 20% MgO, and 20% polyester resin; second composition with a composition of 30% corncob powder, 30% brass powder, 20% MgO, and 20% polyester resin; and third composition with a composition of 40% corncob powder, 20% brass powder, 20% MgO, and 20% polyester resin. Data obtained from the result of research put into a table and displayed in graphical form, then analyzed. Based on this research the conclusion are: (1) Variations composition the brake lining effect on the value of friction coefficient in wet conditions test. This is indicated by the differences of the value of friction coefficient in every specimen composition, where first composition is 0,3447, second composition is 0,4367, and third composition is 0,3653. (2) The most optimal composition when testing in wet conditions is second composition. (3) Corncob fiber brake lining has a good braking performance when testing in wet conditions. At the optimal composition (second composition) the coefficient of friction is higher than Yamaha which has value of friction coefficient is 0,4271.